Value Chain Analysis of Ethiopian Coffee (Coffea arabica) - , Teshale Fekadu Duguma (Archives of Current Research International, 2017)
Ethiopia is well-known as origin of Arabica coffee that produce largely in the country. Coffee plays crucial role in generating foreign currency to the country at large level. Ethiopia’s coffee has its own peculiar quality that produced in the different parts of the country. It is produced in the country in different production system of forest, semi-forest, garden and plantation that made the country unique from other producing countries. Stakeholders like the value chain actors and supporters/facilitators were identified with their role in the chain. Data was collected from both primary and secondary sources from interview of experts and internets, published and unpublished documents respectively. Value chain analysis was undertaken from the collected data to identify the value chain affecting factors. Both qualitative and quantitative analysis tools like, PESTEC, SWOT, matrix, chain map, tables and problem tree were used to identify the possible constraints retarding the performance of the coffee value chain in the country. Factors which were responsible for quality deterioration include; Variety, environmental conditions, agronomical practices, diseases and pest, post-harvest factors and poor marketing infrastructure, crop replacement and adulteration of high quality coffee stated as main factors. To improve the existing coffee value chain performance in terms of quality, all stakeholders need to work in a team spirit with initiatives and supplement inputs and technologies for the producers. Moreover, active quality controlling mechanism by public private partnership should be encouraged by the government.